Pengaturan Kaidah Manajemen Risiko Atas Penawaran Saham Berbasis Teknologi Informasi (Equity Crowfunding) untuk Pengembangan UMKM di Indonesia - Bahtiar, Bahtiar; Lubis, Efridani; Harahap, Hapendi (Jurnal Hukum Jurisdictie, 2021)
Indonesian Government has already put a substantial attention on the development of MSMEs (micro, small, medium enterprises) since the new order regime with regard to the huge number of businessmen and labors involved. Financial technology industry in Indonesia including ECF grows rapidly in recent years but still not supported by a specific constitutional legal standing yet. As part of financial technology products, ECF has been regulated by Indonesian Financial Services Authority in regulation No.57/POJK.04/2020. ECF becomes one of the potential funding sources option for the development of MSMEs and also one alternative for investment purposes in which the issuer offers the sales of equity directly to the investors by using the open network electronic systems. This normative juridical study is aimed to identify the regulation related to risk management, to identify risks in Indonesian ECF’s platform business and risk management regulation setting direction in the future. The aforementioned regulation did not provide risk management guidance for ECF platform. By adopting to the ECF’s platform systematic and comprehensive taxonomy of legally mitigated risks model proposed by Podar Manan et al., the researcher finds at least 12 major risk classification with 42 risk events in Indonesian ECF industry that have to be mentioned and mitigated by the ECF platform. Investors in ECF platforms are exposed to at least 10 risk classification that also have to be considered. Especially for legal risk issues, the researcher identifies at least 11 risk events along with its mitigation initiatives which can be used as reference for the ECF platform.